2014
DOI: 10.4149/neo_2014_069
|View full text |Cite
|
Sign up to set email alerts
|

Expression of serine and glycine-related enzymes in phyllodes tumor

Abstract: Expression patterns of proteins involved in serine and glycine metabolism, and correlations of these patterns with clinicopathologic factors in phyllodes tumor were investigated. Tissue microarrays were prepared from 203 phyllodes tumors (PT) and stained with antibodies specific for glycine decarboxylase (GLDC), phosphoserine aminotransferase 1 (PSAT1), phosphoserine phosphatase (PSPH), phosphoglycerate dehydrogenase (PHGDH), and serine hydroxymethyltransferase 1 (SHMT1). These immunohistochemical results and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
(32 reference statements)
0
16
1
Order By: Relevance
“…In addition, FASN is reported to be involved in tumor progression in various types of neoplasms [19,20], and these facts suggest that lipid metabolism-related proteins play important roles in tumor growth and progression. The metabolism of PT has not been well investigated so far, but in previous studies, the expression of glycolysis-related proteins and serine/glycine metabolism-related proteins were higher in higher grade PTs [11,12], suggesting increased metabolic activity and increased lipid metabolism occur in higher grade PTs. One possible explanation of the differences in metabolic activity according to PT grade is the association between stem cells and metabolism.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, FASN is reported to be involved in tumor progression in various types of neoplasms [19,20], and these facts suggest that lipid metabolism-related proteins play important roles in tumor growth and progression. The metabolism of PT has not been well investigated so far, but in previous studies, the expression of glycolysis-related proteins and serine/glycine metabolism-related proteins were higher in higher grade PTs [11,12], suggesting increased metabolic activity and increased lipid metabolism occur in higher grade PTs. One possible explanation of the differences in metabolic activity according to PT grade is the association between stem cells and metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…Carnitine palmitoyltransferase-1 (CPT-1) [9] and acyl-CoA oxidase 1 (ACOX1) [10] are known to play key roles in β-oxidation. In previous studies, higher expression of glycolysis-related proteins, such as Glut-1, carbonic anhydrase IX (CAIX), and MCT4, was found in PTs of higher grade [11], and the expression of serine/glycine metabolism-related proteins was also higher in higher grade PTs [12]. These results suggest that the expression of lipid metabolism-related proteins may also differ according to PT grade, but there has been no study published to date on this issue.…”
mentioning
confidence: 91%
“…Previous studies have shown that high PSPH expression in many cancers is significantly related to poor prognosis, positive metastasis, and high clinicopathologic stage, including colorectal cancer, phyllodes tumor, breast cancer, Ewing sarcoma, and hepatocellular carcinoma . For example, PSPH contributes to cell survival and proliferation by interacting with c‐MYC under glucose/glutamine deprivation conditions in hepatocellular carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…Although some subsequent studies supported the tumor-promoting effects of GLDC in different cancers such as phyllodes tumor and thyroid cancer [10,12], a recent study provided contradictory evidences for the role of GLDC in gastric cancer, which suggested GLDC might also function as tumor suppressor [31]. Therefore, in spite of the novel increased expression of GLDC in various cancers [9,11,[31][32][33], the functions of GLDC in different kinds of tumors still remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, besides of NSCLC, the increased expression of GLDC was also observed in some other cancers including ovarian cancer, seminoma, invasive lobular carcinoma, and breast cancer [9][10][11]. And the increased expression of GLDC was reported to be associated with the poor prognosis of phyllodes tumor, thyroid cancer, invasive lobular carcinoma, and metastatic breast cancer [11][12][13][14]. However, the roles of GLDC in cervical cancer have never been determined.…”
Section: Introductionmentioning
confidence: 99%